Determinants of modern contraceptive utilization among married women in sub-Saharan Africa: multilevel analysis using recent demographic and health survey - Zemenu Tadesse Tesema; Getayeneh Antehunegn Tesema; Moges Muluneh Boke; Temesgen Yihunie Akalu (BMC, 2022)
Abstract Background Family planning is a low-cost, high-impact public health and development strategy to improve child and maternal health. However, there is a lack of evidence on modern contraceptive use and determinants in sub-Saharan Africa. Hence, this study aimed at determining the pooled prevalence and determinants of modern contraceptive utilization among married women of sub-Saharan Africa. Methods Thirty-six sub-Saharan African countries' demographic and health survey (DHS) data were used for pooled analysis. A total weighted sample of 322,525 married women was included. Cross tabulations and summary statistics were done using STATA version 14 software. The pooled prevalence of modern contraceptive utilization with a 95% Confidence Interval (CI) was reported. Multilevel regression analysis was used to identify the determinants of modern contraceptive use among married women. Four models were fitted to select the best-fitted model using the Likelihood Ratio (LLR) and Deviance test. Finally, the model with the highest LLR and the smallest deviance was selected as the best-fitted model. Results The pooled estimate of modern contraception use in sub-Saharan African countries was 18.36% [95% CI: 18.24, 18.48], with highest in Lesotho (59.79%) and the lowest in Chad (5.04%). The odds of modern contraception utilization were high among women living in East Africa [AOR = 1.47 (1.40, 1.54)], urban areas [AOR = 1.18 (1.14, 1.24)], and women with primary [AOR = 1.49 (1.44, 1.55)] and secondary and above educational level [AOR = 1.66 (1.58, 1.74)]. Moreover, husbands with primary educational level [AOR = 1.38 (1.33, 1.42)], middle [AOR = 1.17, (1.14, 1.21)], rich wealth status [AOR = 1.29 (1.25, 1.34)], media exposure [AOR = 1.25 (1.22, 1.29)], and postnatal care (PNC) utilization [AOR = 1.25 (1.22, 1.29)] had higher odds of modern contraceptive utilization compared with their counter parts. Furthermore, deliver at health facility [AOR = 1.74 (1.69, 1.79)] and birth order 2-4 [AOR = 1.36 (1.31, 1.41)] had higher odds of modern contraceptive utilization. On the other hand, women living in Central [AOR = 0.23 (0.22, 0.24)], Western regions [AOR = 0.46 (0.40, 0.54)], women who decided with husband [AOR = 0.90 (0.87, 0.93)], and decisions by husband alone [AOR = 0.73 (0.71, 0.75)] decreased the odds of modern contraceptive utilization. Conclusion The uptake of modern contraception in sub-Saharan Africa is low. Modern contraceptive utilization is affected by different factors. More attention needs to be given to rural residents, illiterate women, and communities with low wealth status.